1999
DOI: 10.2134/jpa1999.0671
|View full text |Cite
|
Sign up to set email alerts
|

N Fertilization for Pearl Millet Grain in the Southern Coastal Plain

Abstract: Pearl millet (Pennisetum glaucum |R.| Br.) has potential as a grain crop in the U.S. Southeast because it is particularly adapted to acid, sandy Coastal Plain soils. Information is needed, though, on the effect of N fertilization on pearl millet grain and protein yields in the region. We conducted field studies for 2 years at three locations in the Coastal Plain of Georgia to observe pearl millet response to varying rates and times of N fertilizer application. The N‐rate studies included 0, 50, 100, 150, 200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
2
8
1
Order By: Relevance
“…4) show that total protein content increased considerably with increase in nitrogen supply of the growth medium. The results are similar with earlier finding of Menezes et al (1999) working with Pearl Millet (Pennisetum glaucum (R) Br. ): he reported that supra-optimal nitrogen application reduces the growth and grain yield but it caused an increase in protein.…”
Section: Resultssupporting
confidence: 92%
“…4) show that total protein content increased considerably with increase in nitrogen supply of the growth medium. The results are similar with earlier finding of Menezes et al (1999) working with Pearl Millet (Pennisetum glaucum (R) Br. ): he reported that supra-optimal nitrogen application reduces the growth and grain yield but it caused an increase in protein.…”
Section: Resultssupporting
confidence: 92%
“…In Eastern Nebraska, a significant increase in grain yield of pearl millet with application rate of 78 kg N ha -1 was observed by Maman, Mason, Galusha, and Clegg (1999) and Limon-Ortega et al (1998). According to Menezes, Gascho, and Hanna (1999), highest pearl millet yield resulted from N rate of 112 kg ha -1 . On the other hand, N-fertilizer applications have also been reported to be associated with decreased grain yield under late planting situations, drought conditions or high levels of mineral N in soil.…”
Section: Grain Yieldmentioning
confidence: 97%
“…At the Dixon site, the grain N concentration was also slightly higher with cattle manure than with hog manure. Splitting fertilizer N application to increase N supply in the later stage of growth increases grain N concentration in pearl millet (Pennisetum glaucum (R.) Br) in comparison to a single large application at the planting (Menezes et al, 1999). Through slow mineralization, the residual cattle manure may have provided an extended supply of available N to the wheat in the late stages of growth.…”
Section: Nitrogen Harvest Indexmentioning
confidence: 99%